2004
DOI: 10.1103/physreve.70.016103
|View full text |Cite
|
Sign up to set email alerts
|

Geometry effects in confined space

Abstract: In this paper we calculate some exact solutions of the grand partition functions for quantum gases in confined space, such as ideal gases in two-and three-dimensional boxes, in tubes, in annular containers, on the lateral surface of cylinders, and photon gases in three-dimensional boxes. Based on these exact solutions, which, of course, contain the complete information about the system, we discuss the geometry effect which is neglected in the calculation with the thermodynamic limit V → ∞, and analyze the vali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…Dai and Xie [25] derived the exact solutions of the grand partition functions for quantum gases in confined space and discussed the contributions from the geometry effects and the inter-particle interactions to the equation of state. They found that there exists a regime where the geometry effect dominates in an imperfect gas.…”
Section: Interface Effect On Thermodynamics Properties Of Liquid Confmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai and Xie [25] derived the exact solutions of the grand partition functions for quantum gases in confined space and discussed the contributions from the geometry effects and the inter-particle interactions to the equation of state. They found that there exists a regime where the geometry effect dominates in an imperfect gas.…”
Section: Interface Effect On Thermodynamics Properties Of Liquid Confmentioning
confidence: 99%
“…The thermodynamic properties and phase change behavior of fluids confined in very fine spaces have received increasing attention in recent years [23][24][25] . Dai and Xie [25] derived the exact solutions of the grand partition functions for quantum gases in confined space and discussed the contributions from the geometry effects and the inter-particle interactions to the equation of state.…”
Section: Interface Effect On Thermodynamics Properties Of Liquid Confmentioning
confidence: 99%
“…It is assumed that L x and L y are of the micro/nano line dimension and L z is of the macroscopic line dimension. According to Weyl's asymptotic expansion, the grand partition function of the system considered is given by [4] …”
Section: Statistical Characteristics Of An Ideal Fermi Gas In a Confimentioning
confidence: 99%
“…In a recent paper, the thermodynamic properties of an ideal classical gas confined in a narrow box were examined [2]. The approximate solutions of ideal quantum gases confined in a finitesize container were discussed in Lin et al [3], Dai and Xie [4,5], and Su et al [6] and the boundary modifications to the thermodynamic quantities were reported. By using classical gases as the working substance, the influence of the size effect on the performance of the micro-/nanoscaled Carnot cycle [7], regenerative heat engine [8], and Linde-Hampson 230 L. CHEN ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of quantum systems in confined space has been studied for many years in the field of cavity QED [8] and in statistical mechanics [9][10][11][12][13][14][15][16]. The spontaneous emission rate of atoms in a cavity can increase or decrease depending on the shape and size of the cavity [17,18].…”
mentioning
confidence: 99%